Exotic and scandalous. On the reception of Petra Hůlová's literary work in Poland (and the role of a publisher) - Maślanka, Anna (Bohemica Olomucensia, 2023)
The study analyses the reception of Petra Hůlová's literary work in Poland with a focus on her publishers' activities. The writer's books have been published in two different publishing houses - W.A.B., one of the biggest fiction publishers in Poland, and Afera, small publishing house founded by bohemist and translator Julia Różewicz. The author of the paper - basing on the publishers' strategies and the reviews of critics and readers - describes the influence of this transition on the perception of Petra Hůlová's works in Poland and on the position of both writer and publisher in Polish literary field.
Keywords: Petra Hůlová; Czech literature; Czech literature in Poland; literary translation; publisher; literary field